Faktor-Faktor yang Mempengaruhi Efektivitas Penyidikan Pencurian Kendaraan Bermotor: Studi di Kepolisian Resor Bone - Akdar, Andi (CV. Social Politic Genius (SIGn), 2024)
This study aims to examine the effectiveness of the investigation of the criminal offense of motor vehicle theft within the jurisdiction of the Bone Resort Police, as well as the factors that influence this effectiveness. Employing a quantitative descriptive approach, this empirical legal research was conducted at the Bone Resort Police. Data collection methods included questionnaires, documentation, and literature study. The collected data were analyzed using quantitative data analysis techniques. The research findings indicate that the effectiveness of the investigation of motor vehicle theft at the Bone Resort Police is influenced by several factors, namely: the law enforcement structure factor; the legal culture factor; the public legal awareness factor; and the facilities and infrastructure factor. Furthermore, it is assessed that these factors exert a significant influence on the investigation of motor vehicle theft at the Bone Resort Police. It is recommended that police investigators enhance their professionalism to further improve the execution of their duties and authorities in the future.